Identification and characterization of Aspergillus flavus and aflatoxins - Rodrigues, P. (2007)
Aspergillus flavus is the main producer of the well known carcinogenic aflatoxins. The presence of this fungus and aflatoxins is of huge concern in terms of food safety. The identification of A. flavus is not straightforward due to similarities with closely related species (e.g. A. parasiticus and A. nomius). Also, from the biochemical point of view the closely-related species are able to produce different mycotoxins. In order to clarify the differentiation between species the identification schemes is revisited. Selective media, data from mycotoxins production and molecular biology tools are discussed in order to clarify the concept of A. flavus species.